CSR practices of Palestinian Islamic banks: contribution to socio-economic development - Abdalrahman Mohamed Migdad (ISRA International Journal of Islamic Finance, 2017)
Purpose: Corporate social responsibility (CSR) is an important corporate activity that affirms the importance of giving back to the community. This research aims to examine the CSR practices of Palestinian Islamic banks and their contribution to socio-economic development. There is an ongoing debate regarding Islamic financial institutions' profit motive versus their motivation to achieve human welfare. The Palestinian Islamic banks are not disconnected from this debate, and this paper aims to discuss this issue. Design/methodology/approach For The purpose of assessing the CSR practices of Palestinian Islamic banks, a secondary analysis of the banks' annual reports was carried out. In addition, 11 structured interviews were conducted with Islamic banks' practitioners at the decision-making level and with some of the banks' Sharīʿah board members to gather their views on CSR. These have been analyzed in light of the actual CSR practices disclosed in each bank's annual reports. Findings The main research findings suggest that the CSR practice is highly valued by the Palestinian Islamic banks, but it is small and has marginal effects on the community's socio-economic development. Another important observation from report analysis is that Islamic banks have great potential for expansion, given that the demand for Islamic financial transactions is double of what Islamic banks currently offer. If Islamic banks live up to that opportunity, they could deliver more in CSR practices, which is their ultimate goal according to the majority of the interviewees. Originality/value Existing literature has presented findings on the CSR of Palestinian corporations in general, but there is no available literature on the CSR practices of Palestinian Islamic banks. This research attempts to fill in the gap by presenting preliminary findings on Palestinian Islamic banks' CSR practices.
Keywords: 330; community development; corporate social responsibility; Islam; Palestinian Islamic banks; Sharīʿah objectives; socio-economic development